Optimal Two-Degree-of-Freedom Control for Precise Positioning of a Piezo-Actuated Stage - Mohamed Ali, Mohamed Sultan (International Journal of Integrated Engineering, 2017)
Microelectromechanical systems (MEMS) based positioning stages are composed of a piezoelectric actuator (PEA) and a positioning mechanism. Hysteresis is one of the major factors that limit the positional accuracy of piezo-actuated stages. This paper presents a novel method for designing a two-degree-of-freedom (2DOF) controller for precise positioning of a MEMS-based piezo-actuated stage, where Bouc-Wen hysteresis model is used to represent the hysteresis behavior of the PEA. A Luenberger observer-based feed-forward controller is designed, and then integrated with a Particle Swarm Optimization (PSO)-based Proportional-Integral-Derivative (PID) controller to form a 2DOF controller. Optimal PID gains are obtained based on a new fitness function proposed to reduce the displacement error and achieve a fast response time. The results show that using the proposed 2DOF controller reduces the error to be in the range of 0.03 – 1.31% of the maximum displacement when the system is operated in the range of 1 – 50 Hz.